Dose of Trimethoprim-Sulfamethoxazole To Treat Skin and Skin Structure Infections Caused by Methicillin-Resistant Staphylococcus aureus - Cadena, Jose (American Society for Microbiology, 2011)

(untitled)
We undertook this study to investigate whether treatment with a higher dose of trimethoprim-sulfamethoxazole (TMP/SMX) led to greater clinical resolution in patients with skin and soft tissue infections (SSTIs) caused by methicillin-resistant Staphylococcus aureus (MRSA). A prospective, observational cohort with nested case-control study was performed at a public tertiary health system. Among patients with MRSA SSTIs during the period from May 2008 to September 2008 who received oral monotherapy with TMP/SMX and whose clinical outcome was known, the clinical characteristics and outcomes were compared between patients treated with a high dose of TMP/SMX (320 mg/1,600 mg twice daily) for 7 to 15 days and patients treated with the standard dose of TMP/SMX (160 mg/800 mg twice daily) for 7 to 15 days. In patients with MRSA SSTIs, those treated with the high dose of TMP/SMX (n = 121) had clinical characteristics similar to those of patients treated with the standard dose of TMP/SMX (n = 170). The only exception was a higher proportion of patients with a history of trauma upon admission among the patients treated with the higher dose. The proportion of patients with clinical resolution of infection was not different in the two groups (88/121 [73%] versus 127/170 [75%]; P = 0.79). The lack of significance remained in patients with abscess upon stratified analysis by whether surgical drainage was performed. The study found that patients with MRSA SSTIs treated with the higher dose of TMP/SMX (320/1,600 mg twice daily) for 7 to 15 days had a similar rate of clinical resolution as patients treated with the standard dose of TMP/SMX (160/800 mg twice daily) for 7 to 15 days.